2017
DOI: 10.1104/pp.17.01384
|View full text |Cite
|
Sign up to set email alerts
|

Phytochromes and Phytochrome Interacting Factors

Abstract: The basic helix-loop-helix domain-containing transcription factors that interact physically with the red and far-red light photoreceptors, phytochromes, are called PHYTOCHROME INTERACTING FACTORS (PIFs). In the last two decades, the phytochrome-PIF signaling module has been shown to be conserved from Physcomitrella patens to higher plants. Exciting recent studies highlight the discovery of at least four distinct kinases (PPKs, CK2, BIN2, and phytochrome itself) and four families of ubiquitin ligases (SCF EBF 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
397
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(412 citation statements)
references
References 118 publications
(160 reference statements)
8
397
0
7
Order By: Relevance
“…This asymmetrical cell expansion is caused by an auxin maximum in the concave part of the hook, created by auxin influx and outflux carriers (AUXIN1 [AUX1] and LIKE-AUX1, and PIN-FORMED [PIN] proteins, respectively) in the epidermal cells of the young hypocotyl (Box 2; Zádníková et al, 2010Zádníková et al, , 2016Farquharson, 2017). In darkness, PHYTOCHROME INTERACTING FACTORs (PIFs; Box 1; reviewed in this Focus Issue by Pham et al, 2018) enhance auxin synthesis and signaling, and the synthesis of two other important hormones in hook formation and maintenance, ethylene (ET) and gibberellic acid (GA; Box 2; for review, see Mazzella et al, 2014). ET signaling via transcription factors ETHYLENE INSENSITIVE3 (EIN3) and EIN3-LIKE1 (EIL1) induces local PIN gene expression in the epidermis and auxin transport ( Zádníková et al, 2016).…”
Section: The Apical Hookmentioning
confidence: 99%
“…This asymmetrical cell expansion is caused by an auxin maximum in the concave part of the hook, created by auxin influx and outflux carriers (AUXIN1 [AUX1] and LIKE-AUX1, and PIN-FORMED [PIN] proteins, respectively) in the epidermal cells of the young hypocotyl (Box 2; Zádníková et al, 2010Zádníková et al, , 2016Farquharson, 2017). In darkness, PHYTOCHROME INTERACTING FACTORs (PIFs; Box 1; reviewed in this Focus Issue by Pham et al, 2018) enhance auxin synthesis and signaling, and the synthesis of two other important hormones in hook formation and maintenance, ethylene (ET) and gibberellic acid (GA; Box 2; for review, see Mazzella et al, 2014). ET signaling via transcription factors ETHYLENE INSENSITIVE3 (EIN3) and EIN3-LIKE1 (EIL1) induces local PIN gene expression in the epidermis and auxin transport ( Zádníková et al, 2016).…”
Section: The Apical Hookmentioning
confidence: 99%
“…The type of elements found in each gene's promoter region was also different. For example, the PHYB1 promoter region contained 7 G‐Box elements, which bind PHYTOCHROME INTERACTING FACOTRs ( PIFs ) (Pham, Kathare, & Huq, 2018), while in PHYB2, there were only 2. Several other motifs were found only in one or the other phy gene (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that DELLAs interact with AtPIF3 and AtPIF4 and inhibit their activities by sequestering their DNA‐recognition domains, ultimately results in the inhibition of hypocotyl elongation (Feng et al , ; de Lucas et al , ). Excitingly, recent studies have revealed that DELLA proteins negatively regulate PIF accumulation by inducing rapid degradation of PIFs through the 26S proteasome pathway (Li et al , ; Pham et al , ). Indeed, our work showed that GA 3 promotes SlPIF4 protein accumulation, while PAC inhibits SlPIF4 protein accumulation (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, plants have evolved a delicate system that perceives light and temperature signals, allowing them to exquisitely detect and predict changes in the natural environment (Franklin, ). PIFs are basic helix–loop–helix transcription factors and have key roles in light‐regulated plant development and plant responses to multiple environmental signals (Leivar and Monte, ; Leivar and Quail, ; Pham et al , ). PIFs, particularly PIF4, have emerged as a central signalling hub controlling the thermosensory activation of flowering (Kumar et al , ) and thermosensory growth in Arabidopsis (Delker et al , ; Gangappa and Kumar, ).…”
Section: Introductionmentioning
confidence: 99%